Effect of bond-line thickness and mode-mixity on the fracture behavior and traction separation law of Sn-0.7Cu solder joints. (January 2022) - Sharma, Ved Prakash; Datla, Naresh V.
Highlights: Failure of lead-free solder joints studied using both fracture tests and FE model. Bond-line thickness and mode-mixity effects on traction separation law (TSL) studied. Initiation toughness and maximum traction increased only with thickness. Failure behavior correlated with plastic zone and normal stresses ahead of crack. Abstract: In this research, cohesive parameters were extracted for Sn-0.7Cu/Cu solder joint failure. Double cantilever beam (DCB) specimens were used to study the fracture of the joint under both mode-I and mixed-mode conditions. A bilinear traction separation law (TSL) was used to capture the failure of the joint. Increasing the bond-line thickness from 110 to 880 µm increased the critical energy release rate for crack initiation ( Gci ) and maximum traction of the bilinear TSL. This increase in the Gci was attributed to an increase in plastic zone area (PZA) ahead of the pre-crack tip. Varying the mode-mixity with phase angle (ψ) in the range of 0 0 –33 0 showed an insignificant change in Gci and maximum traction of the bilinear TSL.